DNA methylation in Hepatoblastoma-a literature review - Gang Shen; Hongyu Shen; Jing Zhang; Qingtao Yan; Huixian Liu (BMC, 2020)
Abstract Hepatoblastoma (HB) is the most common malignant liver tumor in children. Abnormal activation of the Wnt/β-catenin signaling pathway plays an important role in the formation and development of HB. Genes in HB show a global hypomethylation change, accompanied by hypermethylation of specific tumor suppressor genes (TSGs). This article reviews the hypermethylation changes in several TSGs, such as RASSF1A, SOCS1, APC, HHIP, and P16, and analyzes the pathways and mechanisms of TSGs regulating gene expression. The role of the methylation-regulating enzymes DNA methyltransferases (DNMTs) and ten-eleven translocation (TET) family members enzymes in the methylation changes of HB was analyzed, and it was speculated that the occurrence of HB is partly due to the obstruction of liver differentiation in the early stage of differentiation. The origin cells may be incompletely differentiated hepatocytes remaining in the liver of children after birth. Therefore, further studying the role of methylation regulating enzymes in methylation changes in HB is a promising future research direction.